Mortality pattern in an organized herd of Surti buffaloes of south Gujarat (Indian Journal of Animal Production and Management, 2018)
A retrospective study on mortality pattern in an organized herd of Surti buffaloes maintained at Livestock  Research Station, Navsari Agricultural University, Navsari, Gujarat was carried out using information on  strength at risk, mortality in different groups and causes of mortality over a period of ten years (2005- 2014). Data were collected, analyzed and effect of various risk factors’ (year, sex, age and season on  mortality and causes of mortalities) were studied. Overall mortality over the period of ten years was 2.83  percent. The year-wise mortality varied between 0.87 to 4.61 percent. Comparatively higher mortalities  were observed in males (3.48%) than females (2.45%). The highest mortality was observed in the age  group below one month (6.74%) followed by 1-3 months (2.97%), 6-12 months (1.47%) and 3-6 months  (1.31%) age group. The overall mortality in the age group above one year including adults was only 2.32  percent. The mortalities were the highest in monsoon season (4.49%) followed by winter (2.26%) and least  in summer (1.97%) season. The overall effect of year, age group and season on mortality percent were  highly significant whereas, the effect of sex was non-significant. Of 113 deaths, pneumonia (23.89%) was  the prime cause of mortality followed by deaths due to diarrhoea (15.93%), debility (15.93%), septicemia  (15.04%), accidental deaths (9.74%), blood protozoan infections (6.20%), snake bite (5.30%) and others  (7.98%). Infectious causes were the common causes of deaths in calves below one year compared to  animals above one year indicated improvement in management practices for calves below one year of age.  As mortality rates in Surti buffaloes were significantly higher in calves aged below three months during  monsoon season. Therefore, the higher mortality rates in calves aged below three months during monsoon  season observed in the present study indicates that the care and management of younger buffalo calves  need to be intensified during rainy and early winter seasons due to vulnerability to inclement weather and  infectious diseases in their early life.
Keywords: Causes; Mortality pattern; Surti Buffaloes